Implementation Analysis of PSAK (Financial Accounting Standard) No. 107 at Meulaboh Branch Pawnshop Syariah - Nazri, Cut Kamelia; Vonna, Sari Maulida (Al-Mal: Jurnal Akuntansi dan Keuangan Islam, 2024)
This research examines the application of Sharia Financial Accounting Standards Number 107 at the Meulaboh Branch Pegadaian Syariah. The author employed a qualitative-descriptive research design. Data collecting techniques employed were observation, interviews, and documentation. The analysis reveals that the implemented  PSAK No. 107 at Meulaboh Branch Pegadaian Syariah is not optimum due to a low understanding. Regarding recognition and measurement, the implementation aligns with PSAK No. 107. However, regarding the presentation and disclosure of financial reports, the branch has not fully implemented PSAK No. 107 for not presenting and disclosing financial reports separately.